Learning With Concept Maps And Conference Appproach To The Achievement Of Learning Objectives Clinic - Sunarmi Sunarmi; Dwi Ari Murti; Wiwin Renny Rahmawati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
This study aims to determine the effectiveness of the method of learning with concept maps and conference approach to the achievement of learning objectives Sampling technique was used saturated sampling method. Check-list that is used as an instrument to measure the effectiveness of using concept maps method with the method of the conference to the achievement of learning objectives clinic consisted of 25 item statements. This type of research was a quasi-experimental studies (quasi experiment), using a study design Two Independent-group post-test only. Methods of data analysis in this study using T Test - Test. The results indicate significance level of 5%, calculate r (0001) under the table r (0.05). with the concept map approach is more effective than the methods of the conference.